2016
DOI: 10.1007/s00005-016-0440-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Three CYP2C19 Gene Variants by MassARRAY and Point of Care Techniques: Experience from a Czech Centre

Abstract: Distribution of cytochrome P450 2C19 enzyme gene (CYP2C19) variants affecting metabolism of clopidogrel was determined in 526 Czech patients after percutaneous coronary intervention using MassARRAY genotyping and compared to distribution in other populations of European descent. Fifty-three (10%) patients underwent parallel determination of CYP2C19 genotypes from buccal swabs by a point of care technique with 100% concordance to the main genotyping platform. Observed CYP2C19 genotypes were related to clopidogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Genomic DNA was extracted from 0.5 mL of peripheral blood drawn into EDTA‐coated tubes using QIAamp DNA Blood Mini Kit (Qiagen, Germany). Three single nucleotide polymorphisms (SNPs)—CYP2C19*2 (rs4244285), *3 (rs4986893) and *17 (rs12248560)—were genotyped using Sequenom MassARRAY platform integrating iPLEX (Sequenom Inc, San Diego, CA, USA) based on a previously described method 29 . The assay consists of an initial locus‐specific polymerase chain reaction amplification followed by single base extension reaction using mass‐modified dideoxynucleotide terminators of an oligonucleotide primer that anneals immediately upstream of the target polymorphic site.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from 0.5 mL of peripheral blood drawn into EDTA‐coated tubes using QIAamp DNA Blood Mini Kit (Qiagen, Germany). Three single nucleotide polymorphisms (SNPs)—CYP2C19*2 (rs4244285), *3 (rs4986893) and *17 (rs12248560)—were genotyped using Sequenom MassARRAY platform integrating iPLEX (Sequenom Inc, San Diego, CA, USA) based on a previously described method 29 . The assay consists of an initial locus‐specific polymerase chain reaction amplification followed by single base extension reaction using mass‐modified dideoxynucleotide terminators of an oligonucleotide primer that anneals immediately upstream of the target polymorphic site.…”
Section: Methodsmentioning
confidence: 99%
“…In some acute care settings, it may be important for a quick turnaround time to physically perform the test using an instrument that is in a clinic or inpatient unit. There are a few examples, such as anticipating the need for clopidogrel antiplatelet therapy after percutaneous coronary intervention, when the availability of quick turnaround times in or near the coronary procedure room could facilitate prescribing decisions needed the same day as the procedure (31,102,105,114). Point-of-care testing has also been employed for warfarin (analyzing variants in CYP2C9 and VKORC1), another example when decisions about prescribing and dosing the medication are somewhat urgent (46).…”
Section: Reactive Testingmentioning
confidence: 99%
“…Regarding cardiovascular setting, CYP gene variation plays role in warfarin and clopidogrel metabolism with clear clinical relevance (e.g. [30]). In context of statin adverse drug reaction, Mulder et al [22] reported higher incidence of statin intolerance in the group of patients who carried two of the less effective CYP2D6 *3,*4,*5 alleles.…”
Section: Family Of Cytochrome P450 Genesmentioning
confidence: 99%